Voronoi cells of varieties. (March 2022) - Cifuentes, Diego; Ranestad, Kristian; Sturmfels, Bernd; Weinstein, Madeleine
Abstract: Every real algebraic variety determines a Voronoi decomposition of its ambient Euclidean space. Each Voronoi cell is a convex semialgebraic set in the normal space of the variety at a point. We compute the algebraic boundaries of these Voronoi cells.